GOVT, 10th Edition - Edward I. Sidlow; Beth Henschen (Cengage Learning, 2018)
4LTR Press solutions give students the option to choose the format that best suits their learning preferences. This option is perfect for those students who focus on the textbook as their main course resource. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.